Handbook of formative assessment - Andrade, Heidi L; Cizek, Gregory J (Routledge, 2010)
Formative assessment refers to a wide variety of information gathering activities used to adapt instruction to the current & future needs of students. Included in these activities are traditional classroom tests, observations, oral questioning, class discussions, group & individual projects, & homework
Keywords: Academic achievement -- Testing -- Handbooks, manuals, etc; Educational evaluation -- Handbooks, manuals, etc; Educational tests and measurements -- Handbooks, manuals, etc